Leviathan and the Breast Pump: Toward an Embodied Rhetoric of Wearable Technology. Issue 3 (26th May 2016) - Jack, Jordynn
Abstract : In this essay, I develop a feminist framework for analyzing wearable technologies as embodied rhetorics, one that considers (1) how wearable technologies enable micro-performances of gender, status, and identity; (2) how wearable technologies are embedded in policy/political frameworks as well as scientific/medical ones; (3) how wearable technologies are embedded in spatiotemporal networks of actors, objects, and so on; and (4) how the design of technological objects themselves do or do not live up to the promises of wearability and mobility. Using an analysis of the breast pump as my case and drawing from interviews with women about their experiences, I show how the breast pump crystallizes a network of rhetorics that is both disruptive and productive of gendered differences. In particular, the breast pump presents rhetorical arguments for returning to work soon after childbirth while performing a professional role. At the same time, this technology makes an argument for including nursing bodies on college campuses, spaces that have not historically considered those bodies or their needs.